OPTIMIZATION OF SALES AND COMMUNICATION WORKFLOWS WITH AI: A CASE STUDY ON PRODUCTIVITY GAIN THROUGH CRM INTEGRATION IN HIGH-PERFORMANCE EMAIL CLIENTS - Almeida Barros, Victor (Revista Gênero e Interdisciplinaridade, 2025)
The synergistic integration between Customer Relationship Management (CRM) systems and Artificial Intelligence (AI) has emerged as a transformative factor in optimizing end-user productivity within communication applications, particularly in high-performance sales and customer service contexts. This article presents a systematic literature review (SLR) focused on the last five years (two thousand twenty–two thousand twenty-five), aiming to quantify and qualify the impact of intelligent features (based on AI/ML) and workflow integrations on user productivity and satisfaction in communication tools. The analysis concentrates on how AI, when integrated into CRM platforms (such as HubSpot and Salesforce), automates repetitive tasks, offers predictive insights, and enhances Human-Computer Interaction (HCI), resulting in measurable efficiency gains. Findings indicate that the application of AI in functionalities like optimized message scheduling (SmartSend), automatic email categorization, and response suggestion significantly reduces the time spent per communication transaction, freeing the user for activities of higher strategic value. The SLR methodology allowed for the identification and synthesis of empirical evidence supporting the hypothesis that systems integration is a catalyst for productivity, with direct implications for customer conversion and engagement rates.